A Novel Lactobacilli-Based Teat Disinfectant for Improving Bacterial Communities in the Milks of Cow Teats with Subclinical Mastitis - Yu, Jie; Ren, Yan; Xi, XiaoXia; Huang, Weiqiang; Zhang, Heping (Frontiers in Microbiology, 2017)
Teat disinfection pre- and post-milking is important for the overall health and hygiene of dairy cows. The objective of this study was to evaluate the efficacy of a novel probiotic lactobacilli-based teat disinfectant based on changes in somatic cell count (SCC) and profiling of the bacterial community. A total of 69 raw milk samples were obtained from eleven Holstein-Friesian dairy cows over 12 days of teat dipping in China. Single molecule, real-time sequencing technology (SMRT) was employed to profile changes in the bacterial community during the cleaning protocol and to compare the efficacy of probiotic lactic acid bacteria (LAB) and commercial teat disinfectants. The SCC gradually decreased following the cleaning protocol and the SCC of the LAB group was slightly lower than that of the commercial disinfectant (CD) group. Our SMRT sequencing results indicate that raw milk from both the LAB and CD groups contained diverse microbial populations that changed over the course of the cleaning protocol. The relative abundances of some species were significantly changed during the cleaning process, which may explain the observed bacterial community differences. Collectively, these results suggest that the LAB disinfectant could reduce mastitis-associated bacteria and improve the microbial environment of the cow teat. It could be used as an alternative to chemical pre- and post-milking teat disinfectants to maintain healthy teats and udders. In addition, the Pacific Biosciences SMRT sequencing with the full-length 16S ribosomal RNA gene was shown to be a powerful tool for monitoring changes in the bacterial population during the cleaning protocol.